2019
DOI: 10.1002/jcp.28546
|View full text |Cite
|
Sign up to set email alerts
|

Four novel biomarkers for bladder cancer identified by weighted gene coexpression network analysis

Abstract: Bladder cancer (BC) is one of the most malignancies in terms of incidence and recurrence worldwide. The aim of this study is to find out novel and prognostic biomarkers for patients with BC. First, we identified 258 differentially expressed genes by using GSE19915 from Gene Expression Omnibus database. Second, a total of 33 modules were identified by constructing a coexpression network by using weighted gene coexpression network analysis and yellow module was regarded as the key module. Furthermore, by constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The majority of researchers have just focused on the differential expression of genes associated with BC and have largely ignored the high degree of interconnectivity among genes, where genes with semblable expression patterns might be functionally correlated. Weighted gene co-expression network analysis (WGCNA) is a distinct approach in identifying modules with different categories of correlated genes, and candidate biomarkers or therapeutic targets for cancer management can be picked out according to the connectivity between the internal linkage of the gene sets in specific modules and by calculating the association between the gene sets and related clinical features (6)(7)(8)(9). Furthermore, WGCNA has been successfully applied to identify biomarkers or potential therapeutic targets for BC (8,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of researchers have just focused on the differential expression of genes associated with BC and have largely ignored the high degree of interconnectivity among genes, where genes with semblable expression patterns might be functionally correlated. Weighted gene co-expression network analysis (WGCNA) is a distinct approach in identifying modules with different categories of correlated genes, and candidate biomarkers or therapeutic targets for cancer management can be picked out according to the connectivity between the internal linkage of the gene sets in specific modules and by calculating the association between the gene sets and related clinical features (6)(7)(8)(9). Furthermore, WGCNA has been successfully applied to identify biomarkers or potential therapeutic targets for BC (8,10).…”
Section: Introductionmentioning
confidence: 99%
“…Weighted gene co-expression network analysis (WGCNA) is a distinct approach in identifying modules with different categories of correlated genes, and candidate biomarkers or therapeutic targets for cancer management can be picked out according to the connectivity between the internal linkage of the gene sets in specific modules and by calculating the association between the gene sets and related clinical features ( 6 9 ). Furthermore, WGCNA has been successfully applied to identify biomarkers or potential therapeutic targets for BC ( 8 , 10 ). Hence, we attempt to construct a network through a comprehensive bioinformatics method in the light of WGCNA and identified prognostic genes of BC.…”
Section: Introductionmentioning
confidence: 99%
“…In present, WGCNA has been widely used to screen out novel and effective molecular biomarkers in bioinformatics eld [28,29]. In our previous study, we have made great efforts to use WGCNA as the main method to identify prognosis biomarkers for bladder cancer [30]. Thus, we rstly identi ed genes associated with survival of ACC in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] In addition, the study of Yan X had demonstrated that CCNB1 was a key gene and associated with the prognosis of BC. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%